Head and neck surgery - Ferris, Robert L. (Master techniques in otolaryngology--head and neck surgery, 2013)
V. 1. Larynx, hypopharynx, oropharynx, oral cavity and neck -- v. 2. Thyroid, parathyroid, salivary glands, paranasal sinuses and nasopharynx